Pedagogia hospitalar: a prática pedagógica no espaço Acolher da fundação Santa Casa de Misericórdia do Pará - GOMES, Thais Mota (2022)
The present study is based on the scope of Hospital Pedagogy and aims to understand the role of the pedagogue in the non-school environment, as well as highlighting its importance for children who undergo long periods of treatment resulting from scalping, thus being able to be absent for some time. school and their family environment. The objective of this study is to understand the didactic-pedagogical work that the hospital pedagogue develops in the context of teaching and learning processes in the hospital environment. Methodologically, qualitative research was carried out in the bibliographic and documentary scope, as well as interviews. Highlighting the educational actions that were created to serve the scalped children who are inside the Espaço Acolher, given all the fragility, low self-esteem, fear and anguish they feel. Therefore, it is possible to observe the benefits, both in the learning of these children and in the emotional and social aspects, that the work of the educator can provide to these children who are undergoing treatment.